Additive negative effects of decadal warming and nitrogen addition on grassland community stability. (28th February 2020) - Wu, Qian; Ren, Haiyan; Wang, Zhongwu; Li, Zhiguo; Liu, Yinghao; Wang, Zhen; Li, Yuanheng; Zhang, Ruiyang; Zhao, Mengli; Chang, Scott X.; Han, Guodong
Abstract: Much recent research has explored how global warming and increased nitrogen (N) deposition, two important components of global environmental changes, influence the structure and functioning of natural ecosystems. However, how ecosystem dynamics respond to the combination of long‐term warming and N enrichment remains largely unexplored. We investigated the impact of warming and N addition on the temporal stability of plant communities in a decade‐long field experiment, conducted in a desert steppe in northern China, using a split‐plot design with warming as the main‐plot factor and N addition as the split‐plot factor. Long‐term warming and N addition had additive, negative effects on plant community stability. A warming‐induced decrease in species richness was not a significant driver of decreased community stability, which was instead driven by the decreased stability of dominant species under warming. On the other hand, a N‐induced decrease in community stability was ascribed to both decreased stability of dominant and common species and decreased asynchronous population dynamics under N addition. Synthesis. Our results suggest that ongoing anthropogenic environmental changes may have appreciable consequences for the stability of natural grassland functions and services while also highlighting the different mechanisms associated with the similar effects of climate warming and increased N deposition on grassland community stability. Abstract : Our results suggest that ongoing anthropogenic environmental changes may have appreciable consequences for the stability of natural grassland functions and services while also highlighting the different mechanisms associated with the similar effects of climate warming and increased N deposition on grassland community stability. Editor's Choice 摘要: 近年来，许多研究已经探讨了全球变暖和大气氮沉降增加这两个全球变化重要组成部分如何影响自然生态系统的结构与功能。然而，生态系统动态变化对长期增温和氮素增加共同的响应仍存在许多未知。 我们在中国北方荒漠草原进行了为期十年的野外观测试验去研究增温和氮素添加对植物群落时间稳定性的影响。该试验采用裂区设计，增温作为主处理，施氮作为副处理。 长期增温和氮素添加对植物群落稳定性有累加的负效应。增温引起的物种多样性的降低并不是群落稳定性降低的显著驱动因子，增温下植物群落稳定性降低是由优势种的稳定性降低所导致的。另一方面，氮素添加引起的群落稳定性的降低是由优势种和常见种稳定性的降低和物种异步性降低所导致的。 我们的结果表明，持续的环境变化可能对天然草地生态系统功能和服务有显著的影响，本研究同时也强调了气候变暖和氮沉降增加对草地群落稳定性的相似影响存在着不同的响应机制。